USING SHOW AND TELL (S&T) STRATEGY IN TEACHING VOCABULARY AT THE SECOND GRADE STUDENTS OF JUNIOR HIGH SCHOOL (MTS) ASSHOLIHIYAH LINGKOK LEKONG EAST LOMBOK IN THE ACADEMIC YEAR 2023/2024 - Wahab, Abdul (P@RAD!GMA : Jurnal Kajian Budaya & Media, 2023)
The aim of this study is to analyze of The Use of Show And Tell (S&T) Strategy in Teaching Vocabulary at the Second Grade Students of Junior High School (MTs) Assholihiyah Lingkok Lekong East Lombok in the Academic Year 2023/2024. The design of this research is Quasi Experimental Design, with experimental and control class. The data are collected by using observation and questionnaire. The populations are 38 students which consist of 19 students as experimental class and 19 students as a control class. The result of the data indicated that there is a significant difference between student’s post-test in experimental class and controlled class. The mean score of post-test (9.02) in experimental class was higher than the mean score of post-test (5.63) in controlled class. Through t-test (14.2) was higher than t-table (2.042) at the level of significance 0.05 with degree of freedom are 36. It concluded that, the hypothesis on this study is accepted. Meaning that, by using Show & Tell (S&T) method is effective towards the students vocabulary mastery at the second Year Students of Junior High School (MTS) Assholihiyah Lingkok Lekong East Lombok. Therefore, the English teacher may use Show & Tell (S&T) Method in teaching English process. Because it can make the English learning process more enjoyable, fun and effective.